MODERN APPROACHES IN INTERNATIONAL TRANSLATIONS - Shohida Otaxanova, Shohida Otaxanova (Журнал иностранных языков и лингвистики, 2021)
In this article the authors highlighted some problems and difficulties while translating from one language into another. Especially it is vividly seen when it depends on the choice of all the principles of translation.